표준보육과정에 기초한 영아관찰척도 개발을 위한 기초 연구 - 강현미(Hyun Mi Kang); 황해익(Hae Ik Hwang) (Korean Journal of child studies, 2011)
The purpose of this study is to develop a valid and reliable infant observation scale based on the national curriculum for childcare centers. The study was carried out using the final draft of the Infant Observation Scale for 1 year old infants. The scale consists of 42 items in 6 areas. Whereas the final draft of the Infant Observation Scale for 2 year old infants consists of 52 items in 6 areas. The subjects of this observation scale were 120 infants from the city of Busan. The results of the Infant Observation Scale for the 1 year old infant analysis for the purpose of test adequacy indecates that the internal consistency reliability is from .88 to .97. The results of the Infant Observation Scale for 2 year old infant analysis for test adequacy shows that the internal consistency reliability is from .76 to .97.